Kinetic insights into Ag-doped TiO2 photocatalysts for dye degradation: advances in materials driving renewable energy technologies - Din, Imad Ud; Saad, Laila; Rehman, Zia Ur; Gul, Fazal Suhrab; Rehman, Najeeb Ur; Mabood, Fazal; Shahzad, Adnan; Wang, Penggang; Al-Saeedi, Sameerah I.; Zaki, Magdi E. A. (Frontiers in Catalysis, 2026)
IntroductionWater pollution, stemming from various sources such as pharmaceuticals waste, pesticides, herbicides, textile dyes, resins, and phenolic compounds, is a significant concern in today’s world. Even small amounts of water pollutants can have detrimental effects on human health and ecosystems. Therefore, proper treatment of industrials wastewater through sewage treatment plants is essential for effective wastewater management.MethodIn this study, undoped TiO2 and silver-doped TiO2 nanoparticles were synthesized via Sol-Gel method and thoroughly characterized using X-Ray Diffraction (XRD), UV-Visible Spectroscopy, Scanning Electron Microscopy (SEM), Energy Dispersive X-rays (EDX), and Fourier Transform Infrared Spectroscopy (FT-IR).ResultsResults revealed a red shift in the UV-Visible spectrum, with increasing silver percentage (2%–4% weight), and silver doping effectively tuned the band gap from undoped TiO2 from 3.03 eV to 2.47. XRD analysis revealed an average crystallite size range of 8–12 nm. SEM studies demonstrated morphological changes due to doping, while EDX confirmed the elemental composition of the nanoparticles. FT-IR analysis affirmed sample purity and vibrations of the required functional groups.DiscussionThe synthesized nanoparticles exhibited efficient degradation of Malachite Green and Rose Bengal dyes under varied conditions, with 2% weight TiO2 displaying the highest Photodegradation Efficiency (PDE) of 98% for Malachite Green at optimal conditions of 4 mg catalyst concentration, 85 μM dye concentration, and pH 9 and 2 mg catalyst concentration, 10 μM dye concentration, and pH 3 for Rose Bengal. Kinetic analysis revealed pseudo first order kinetics with observed rate constant of 0.9438 min-1 for Malachite Green and 0.18118 min-1 for Rose Bengal, supporting the efficiency of heterogeneous photocatalysis for wastewater treatment. This study underscores the significance of the optimizing degradation parameter for practical applications.